Topographic Control on Ground Motions and Landslides From the 2015 Gorkha Earthquake. Issue 10 (17th May 2022) - Dunham, Audrey M.; Kiser, Eric; Kargel, Jeffrey S.; Haritashya, Umesh K.; Watson, C. Scott; Shugar, Dan H.; Hughes, Amanda; DeCelles, Peter G.
Abstract: Landslides triggered by earthquake shaking pose a significant hazard in active mountain regions. Steep topography promotes gravitational instabilities and can amplify the seismic wavefield; however, the relationship between topographic amplification and landsliding is poorly understood. Here, we use numerical methods to investigate the link between low‐frequency ground shaking, topographic amplification, and the landslide distribution from the 2015 Gorkha, Nepal earthquake. Results show that the largest landslides initiated where the highest topographic amplification, highest elevations, and steepest slopes converged, typically in glacially‐sculpted terrain, with additional controls of rock strength and absolute ground motions. Additionally, the initiation of the largest and most fatal landslide was likely influenced by amplification throughout the rupture due the orientation of the ridge with respect to the propagating wavefield. These results indicate that topographic amplification is one of the key factors for understanding where large and potentially devastating landslides are likely to occur during future major earthquakes. Plain Language Summary: Coseismic landslides, or landslides that happen because of earthquake shaking, can cause more damage and devastation to communities than the earthquake shaking itself. One potential cause of coseismic landslide initiation is increased seismic amplitudes at the tops of ridges due to constructive interference of seismic waves within a ridge, a phenomenon known as topographic amplification. The shaking from the 2015 Gorkha earthquake in Nepal caused 25, 000 coseismic landslides. In this study, we model the ground shaking caused by the earthquake to isolate how topography affects the amplitudes of seismic waves and whether this contributed to landsliding. We find that topographic amplification plays an important role in initiating the largest landslides and that continual amplification of one ridge throughout the earthquake influenced the initiation of the largest and most fatal landslide. Modeling topographic amplification from future earthquakes could improve our estimates of where the largest and most devastating landslides are likely to occur. Key Points: Initiation of the largest coseismic landslides corresponds to high topographic amplification, steep slopes, and high elevations The initiation of the Langtang Valley landslide was likely influenced by multiple episodes of amplification throughout the rupture Characterizing topographic amplification can provide insight into where large landslides are likely to occur during future earthquakes